Bacterial Origin and Community Composition in the Barley Phytosphere as a Function of Habitat and Presowing Conditions - Normander, Bo (American Society for Microbiology, 2000)
An understanding of the factors influencing colonization of the rhizosphere is essential for improved establishment of biocontrol agents. The aim of this study was to determine the origin and composition of bacterial communities in the developing barley (Hordeum vulgare) phytosphere, using denaturing gradient gel electrophoresis (DGGE) analysis of 16S rRNA genes amplified from extracted DNA. Discrete community compositions were identified in the endorhizosphere, rhizoplane, and rhizosphere soil of plants grown in an agricultural soil for up to 36 days. Cluster analysis revealed that DGGE profiles of the rhizoplane more closely resembled those in the soil than the profiles found in the root tissue or on the seed, suggesting that rhizoplane bacteria primarily originated from the surrounding soil. No change in bacterial community composition was observed in relation to plant age. Pregermination of the seeds for up to 6 days improved the survival of seed-associated bacteria on roots grown in soil, but only in the upper, nongrowing part of the rhizoplane. The potential occurrence of skewed PCR amplification was examined, and only minor cases of PCR bias for mixtures of two different DNA samples were observed, even when one of the samples contained plant DNA. The results demonstrate the application of culture-independent, molecular techniques in assessment of rhizosphere bacterial populations and the importance of the indigenous soil population in colonization of the rhizosphere.